Onfarm technology testing: for whom? what? and how? - Ezumah, H. (1991)
On-farm research is aimed at developing technologies well match the goals and environment of farmers. At its various stages of diagnosis, choice of techniques, testing and validating technologies, ones would always ask questions: what technologies are developed, for whom and how? In this paper methodological questions are examined with emphasis on the testing stage by means of a case-study of cassava-based farming systems research at Ohosu, in South-Western Nigeria by the on-farm research team of UTA's Resource and Crop Management programme.